Effect of planting distance and pinching on growth, flowering and yield of China aster (Callistephus chinensis.) cv. Poornima - KHOBRAGADE, RAJESH KUMAR; BISEN, SHARAD; THAKUR, RAJENDRA SINGH (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted to study the effect of planting distance and pinching on growth, flowering and yield of China aster (Callistephus chinensis L. Nees.) cv. Poornima. The experiment consisted of six spacing (20 × 10, 30 × 10, 40 × 10, 30 × 20, 30 × 30, 40 × 20;) and with unpinched and pinched and laid out in factorial randomized block design with two replications. The closer spacing 20 cm × 10 cm produced taller plants (86.74 cm) and flower production was higher / unit area then wider spacing. Pinching reduced the plant height and delayed flowering. Pinched plant yield more than unpinched plant. The interaction of spacing and pinching was found that closer spacing with pinching gave higher yield (56.75 kg/plot) and economically best than wider spacing with unpinched plants. Wider spacing with pinched plants given more number (60.90), weight (381.05 g/plot) and diameter (5.90 cm) of flowers.